Geostatistical Analysis and Mapping of Malaria Risk in Children under 5 Years Old in Togo - Sanoussi, Yacobou; Dandonougbo, Yevessé; Tossou, Yaovi (DEMO, 2022)
The objective of this research is to analyze the geostatistical and cartographic determinants of malaria risk among children under 5 years of age in Togo. Using a geostatistical model and data from the 2017 MIS survey in Togo, the results reveal that children of uneducated mothers have a higher malaria prevalence than those of educated mothers. The general trend observed is that households living in urban areas have a lower prevalence of malaria compared to those living in rural areas. The prevalence of malaria among children under five years old decreases with increasing household wealth. Malaria prevalence was also positively associated with vegetation index and minimum temperature. Thus, these results suggest the need for effective and efficient public health interventions in high-risk areas. In addition, the determinants of malaria spatial distribution identified in this study together with the established malaria risk maps could be used in the implementation of malaria control programs and policies to define priority intervention areas.(original abstract)
Keywords: Geostatistics; Risk; Illness; Health; Children